Effects of photochemical oxidation on the mixing state and light absorption of black carbon in the urban atmosphere of China - Qiyuan Wang; Rujin Huang; Zhuzi Zhao; Junji Cao; Haiyan Ni; Xuexi Tie; Chongshu Zhu; Zhenxing Shen; Meng Wang; Wenting Dai; Yongming Han; Ningning Zhang; et al. (Environmental Research Letters, 2017)
The relationship between the refractory black carbon (rBC) aerosol mixing state and the atmospheric oxidation capacity was investigated to assess the possible influence of oxidants on the particles’ light absorption effects at two large cities in China. The number fraction of thickly-coated rBC particles ( F _rBC ) was positively correlated with a measure of the oxidant concentrations (OX = O _3 + NO _2 ), indicating an enhancement of coated rBC particles under more oxidizing conditions. The slope of a linear regression of F _rBC versus OX was 0.58% ppb ^−1 for Beijing and 0.84% ppb ^−1 for Xi’an, and these relationships provide some insights into the evolution of rBC mixing state in relation to atmospheric oxidation processes. The mass absorption cross-section of rBC (MAC _rBC ) increased with OX during the daytime at Xi’an, at a rate of 0.26 m ^2 g ^−1 ppb ^−1 , suggesting that more oxidizing conditions lead to internal mixing that enhances the light-absorbing capacity of rBC particles. Understanding the dependence of the increasing rates of F _rBC and MAC _rBC as a function of OX may lead to improvements of climate models that deal with the warming effects, but more studies in different cities and seasons are needed to gauge the broader implications of these findings.